Mapping seabird vulnerability to offshore wind farms in Norwegian waters - Per Fauchald; Victoria Marja Sofia Ollus; Manuel Ballesteros; Arild Breistøl; Signe Christensen-Dalsgaard; Sindre Molværsmyr; Arnaud Tarroux; Geir Helge Systad; Børge Moe (Frontiers in Marine Science, 2024)
Introduction Offshore wind energy development (OWED) has been identified as a major contributor to the aspired growth in Norwegian renewable energy production. Spatially explicit vulnerability assessments are necessary to select sites that minimize the harm to biodiversity, including seabird populations. Distributional data of seabirds in remote areas are scarce, and to identify vulnerable areas, species, and seasons it is necessary to combine data sets and knowledge from different sources. Methods In this study, we combined seabird tracking data, data from dedicated coastal and seabird at-sea surveys, and presence-only data from citizen science databases to develop habitat suitability maps for 55 seabird species in four seasons throughout the Norwegian exclusive economic zone; in total 1 million km 2 in the Northeast Atlantic. The habitat suitability maps were combined with species-specific vulnerability indicators to yield maps of seabird vulnerability to offshore wind farms (OWFs). The resulting map product can be used to identify the relative vulnerability of areas prospected for OWED with respect to seabird collision and habitat displacement. More detailed assessments can be done by splitting the spatial indicators into seasonal and species-specific components. Results and discussion Associated with higher diversity of seabirds near the coast, the cumulative vulnerability indicator showed a strong declining gradient from the coast to offshore waters while the differences in vulnerability between ocean areas and seasons were negligible. Although the present map product represents the best currently available knowledge, the indicators are associated with complex uncertainties related to known and unknown sampling biases. The indicators should therefore be used cautiously, they should be updated regularly as more data become available, and we recommend that more detailed environmental impact assessments based on dedicated seabird surveys, tracking of birds from potentially affected populations and population viability analyses are conducted in areas ultimately selected for OWED.

Kites Milvus migrans lineatus (Milvus migrans migrans/lineatus) are spreading west across Europe - Mykola Skyrpan; Connor Panter; Winfried Nachtigall; Romain Riols; Geir Systad; Jan Škrábal; Ivan Literák (Journal of Ornithology, 2021)

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Individual migration strategy fidelity but no habitat specialization in two congeneric seabirds - Benjamin Merkel; Sébastien Descamps; Nigel G. Yoccoz; David Grémillet; Francis Daunt; Kjell E. Erikstad; Aleksey V. Ezhov; Mike P. Harris; Maria Gavrilo; Svein‐Håkon Lorentsen; Tone K. Reiertsen; Harald Steen; et al. (Journal of Biogeography, 2021)
Aim In migratory species, individuals often use fixed and individual‐specific migration strategies, which we term individual migration strategy fidelity (IMSF). Our goal was to test if guillemots have flexible or fixed individual migration strategies (i.e. IMSF), if this behaviour is consistent across large parts of the genus’ range and if they were philopatric to geographical sites or a habitat feature. Location North Atlantic. Taxon Uria spp. Methods We quantified consistent individual differences in inter‐annual spatial distribution and habitat occupied throughout the non‐breeding period using a large geolocator tracking dataset of 729 adult seabirds breeding at 13 colonies across the Northeast Atlantic and repeatedly tracked up to 7 years over a 9‐year period. Additionally, we used a similarity index to calculate relative fidelity to either geographical sites or habitats and linear mixed‐effects models to assess persistence of spatial site fidelity over multiple years. Results Both guillemot species exhibited IMSF across a large part of the genus’ range which persisted over multiple years. Individuals of both species and almost all colonies showed fidelity to geographical sites and not to specific habitats. Main conclusions Guillemots show IMSF that is best explained by site familiarity (fidelity to specific sites) rather than habitat specialization (fidelity to specific habitats). In the context of rapidly changing environments, favourable habitats may permanently shift locations and hence species displaying IMSF driven by site familiarity—such as the genus Uria —may not be able to adjust their migration strategies sufficiently fast to sustain individual fitness and ensure population persistence.

Natal dispersal of black kites from Slovakia - Ivan Literák; Miloš Balla; Stanislav Vyhnal; Jan Škrábal; Lubomír Peške; Peter Chrašč; Geir Systad (Biologia, 2020)

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

Migration patterns, breeding and moulting locations of king eiders wintering in north-eastern Norway - Jan Ove Bustnes; Anders Mosbech; Christian Sonne; Geir Helge Systad (Polar Biology, 2010)